Cut free sequent calculus for logic S5n(ED) - Giedra, Haroldas (Lietuvos matematikos rinkinys, 2010)
Hilbert style, Gentzen style sequent and Kanger style sequent calculi for logic S5n(ED) are considered in this paper. Gentzen style sequent calculus is constructed and its equivalence with Hilbert style system is proved, getting soundness and  completeness of Gentzen style system. Kanger style indexed sequent calculus is defined for cut elimination.
Keywords: epistemic logic; distributed knowledge; knowledge of everybody; sequent calculus; cut elimination